The application of Halal logistic in Korean Halal industry: a model from Malaysia perspective - Taegeun, Kim; Saffinee, Siti Syahirah; Jamaludin, Mohd Aizat (HH Publisher, 2019)
Since the emergence of the “halal” industry, it has influenced the pre-existing industrial structure by inducing global corporations and foreign governments to chase the regulation of “halal” certificate. In accordance with the fundamental notion of the “halal” industry, Majority of works related to “halal” industry must retain “halal” certificate regulated by certification bodies of diverse countries. Countless corporations that have the intention to advance into “halal” market started to dive into building plan of the domestic “halal” industry by complying conditions required by “halal” regulation and “halal” logistics is one of them esteemed to account for crucial status in near future among each section of “halal” industry on the side of conveyance of “halal” products. Nonetheless, it has not been perfectly settled up in the global “halal” industry so far due to underestimation of the importance of “halal” logistics compared with other sections belonged in the “halal” industry. Especially this feature predominantly reveals in Korea because of less “halal” perception of the domestic workers. Korea is one of the nations ached for participating in the “halal” market in the same way as other west unions and Asian countries which are not Islamic nations. Although there is the highlight of the “halal” industry from government and private companies, less infrastructure and information of “halal” industry are still barrier on the position of Korea and aspect of adjusting “halal” compulsory into the domestic industry. Not only them but also the absence of expert are on the issue because of the influx of uncertain notion and technique of “halal” into Korea. Besides “halal” logistics is also clumsy industrial part to Korea and the various environment which is engaged in the logistics industry includes not only technical parts but also policies. So as to contribute to making up of the definite establishment of “halal” logistics for the pre-existing industry of Korean logistics, the criterion of this research is based on MS 2400:2010 and pre-existence manual of Korean logistics industry which is allocated to every single factor consisting of the extant environment of logistics in Korea. Thus, this research denotes veiled factors which are not adjustable to “halal” logistics by analyzing the current status of Korean logistics by adding a comparison between MS 2400: 2010 and present status of domestic logistics.